English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

-x^2 -6x +7

2007-03-09 03:20:46 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

-x^2 - 6x + 7

Your first step is to factor (-1) out of the trinomial.

(-1)(x^2 + 6x - 7)

Now, factor normally.

(-1)(x + 7)(x - 1)

2007-03-09 03:23:50 · answer #1 · answered by Puggy 7 · 0 0

-(x - 1)(x + 7) = -(x^2 + 6x -7)
wondering y?

here the trinomial has a form of:

a+b+c =0

where a=1, b=6, and c= - 7 in this problem
This kind of trinomials always have two roots
x1 = 1 and the other is x2 = c/a = -7

In term of factor: ( x- x1)(x-x2)
or (x-1)(x +7)

that is how the factor come from, and dont forget the negative sign in front of the bracket.

2007-03-09 03:35:13 · answer #2 · answered by tuoidabuon 2 · 0 0

= - (x² + 6x - 7)
= - (x + 7).(x - 1)
= (x + 7).(1 - x)

2007-03-09 04:08:45 · answer #3 · answered by Como 7 · 0 0

fedest.com, questions and answers